Dinâmica geoeconômica da indústria farmacêutica: inovação, mercado e consumo dos psicotrópicos - Halas, Geizibel Julia (2021)
The pharmaceutical sector is one of the largest investors in R&D in the world; in 2018 alone, $172 billion was allocated for research and innovation. It is the new products that leverage the profit rates of this segment; the world drug market reached US$ 1.74 trillion in sales in 2020. The present work has the general objective of understanding the geo-economic dynamics of the pharmaceutical industry, including the innovation, production, and consumption of psychotropic drugs. To this end, we used data on the production and consumption of psychotropic drugs coming only from the industrial sector - the compounding pharmacy sector was excluded - because their spatial integrations differ substantially from those performed in pharmaceutical laboratories. The genesis and development of the sector and the relations between space, industry and consumption of psychotropic drugs are presented, demonstrating the geographic relationship established in this economic sector and, thus, its geo-economic dynamics.